Career-mother in Indonesian Soap Opera: A Counter-stereotype Representation - Aditya Fahmi Nurwahid (ETTISAL : Journal of Communication, 2021)
Abstract Motherhood becomes one of the major representations in television by the fiction program stories and narratives. Based on this phenomenon, it is important for television built and portrayed the figure of mother via their program. There are several researches about the portrayal of women on television. But, still few study that exposes the portrayal of the mother and her career, especially in Indonesia. This research will expose the mother and work culture representation in the television soap opera, using the Gamson and Modigliani framing scheme. This research takes three of the popular soap opera in Indonesia from 2015-2019. For the result, there are several depictions of mothers and her career in soap operas. Plot, text, and framing scenes affects or negotiates the ideal value of career mother with counter-stereotypes representation and new value representation. But, these soap opera seems only use the counter-value representation to differentiate their serial with others. Abstrak Sosok ibu menjadi salah satu representasi yang banyak ditemui di sinetron yang ditayangkan televisi. Berdasarkan fenomena ini, penting bagi televisi untuk membangun dan menangkap sosok ibu melalui program mereka. Telah banyak riset mengenai representasi ibu di televisi, namun hanya sedikit yang mengekspos bagaimana ibu karier ditampilkan, terutama di Indonesia. Penelitian ini akan melihat bagaimana representasi ibu dan pekerjaan dalam sinetron di Indonesia. Menggunakan skema framing yang diperkenalkan Gamson dan Modigliani, penelitian ini akan melihat representasi melalui tiga sinetron paling populer sepanjang 2015-2019. Hasilnya, terdapat beberapa gambaran dari ibu dan kariernya di dalam sinetron. Plot, teks, dan pembingkaian dalam tampilan akting turut mempengaruhi nilai ideal dari sosok ibu karier. Sinetron juga turut menampilkan representasi yang melawan stereotip serta nilai baru terkait peran ibu karier. Hanya saja, sinetron tampak menampilkan representasi tersebut untuk membedakan ceritanya dengan sinetron lain.